Evaluation of water-soluble dyes to mark internal structures of Lepidoptera via larval feeding - Rezende, Gabriel Fernandes [UNESP]; Fernandes, Odair Aparecido [UNESP] (FapUNIFESP (SciELO), 2024)
Understanding aspects of insect ecology is a key component for the applicability of control methods or pest resistance management. For instance, the comprehension of insect dispersal is crucial to determining insect gene flow and the maximum distance between refuge areas in Bt (Bacillus thuringiensis) crops. But, for such studies, insects need to be marked prior to release. Seeking to refine the technique of dispersion studies of the genetic material of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), this study aimed to determine the efficiency of water-soluble dyes for the internal marking of S. frugiperda immatures and adults via larval feeding, with emphasis on marking the spermatophore. Rhodamine B, Methylene Blue, Ponceau, Coomassie, and Eosin-Nigrosin were added to the larval artificial diet at concentrations of 0, 100, 200, 400, 600, 800, and 1000 ppm. Mortality and duration of the larval stage as well as the efficiency of marking internal structures of larvae and adults were evaluated. Rhodamine B and Methylene Blue increased the duration of the larval period, but the former caused higher mortality. The staining of the gut, hemolymph, and imaginal discs, in the larval phase, was observed for Rhodamine B, Methylene Blue, and Coomassie dyes. However, none of the dyes were efficient for marking spermatophores. Thus, the addition of these water-soluble dyes to the larval diet of S. frugiperda can mark internal structures of the larva, but not the adult. Therefore, these dyes have limited application once they may be used only for marking larvae.
Keywords: Insect movement Gene flow Mark-capture technique Spatial distribution